Aetiology of acute diarrhoea in adults. Issue 5 (May 1981) - Jewkes, J; Larson, H E; Price, A B; Sanderson, P J; Davies, H A
Abstract : We have studied 73 adults with acute diarrhoea and identified a micro-organism or toxin likely to be the cause in 58%. In addition to routinely cultured bacteria, Campylobacter coli/jejuni and Clostridium difficile were important pathogens in the community. Patients who developed diarrhoea after antibiotic use had a distinctive clinical syndrome and comprised the third largest group of cases. Clinical, epidemiological, and histological features in an additional group with negative cultures and no antibiotic history suggest that an additional bacterial pathogen remains to be identified as a cause of acute diarrhoea in adults.